Mass Spectrometry Based Molecular 3D-Cartography of Plant Metabolites - Floros, Dimitrios J.; Petras, Daniel; Kapono, Clifford A.; Melnik, Alexey V.; Ling, Tie-Jun; Knight, Rob; Dorrestein, Pieter C. (Frontiers in Plant Science, 2017)
Plants play an essential part in global carbon fixing through photosynthesis and are the primary food and energy source for humans. Understanding them thoroughly is therefore of highest interest for humanity. Advances in DNA and RNA sequencing and in protein and metabolite analysis allow the systematic description of plant composition at the molecular level. With imaging mass spectrometry, we can now add a spatial level, typically in the micrometer-to-centimeter range, to their compositions, essential for a detailed molecular understanding. Here we present an LC-MS based approach to 3D plant imaging, which is scalable and allow the analysis of entire plants. We applied this approach in a case study to pepper and tomato plants. Together with MS/MS spectra library matching and spectral networking, this non-targeted workflow provides the highest sensitivity and selectivity for the molecular annotations and imaging of plants, laying the foundation for studies of plant metabolism and plant-environment interactions.